SAPARD Programme and Its Implementation in Tourism Development in Bistrita-Nasaud County, Romania - Cocean, Pompei; Ilovan, Oana-Ramona (Journal for Geography, 2009)
Our analysis focused on emphasizing the manner of attracting the financial resources in the sector of tourism in a particular territorial entity (Bistria-Nsud County, situated in northern Romania, in the Northwest Development Region), where small private initiatives were representative for Romania’s approach to this sector. Sustainable rural development was partly triggered by the implementation of the SAPARD programme during the pre-accession period of Romania to the European Union. Focusing on sustainable tourism in the countryside andBistria-Nsud County was another such example.
Keywords: recent tourism development; impact; feedback